PENGARUH DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA GURU YANG DIMODERASI SUPERVISI KEPALA SEKOLAH DI SMA NEGERI DI KABUPATEN JEPARA - Setyo Harno, 11.52.02.0019 (Students Journal of Economic and Management, 2013)
This research is aimed to analyze the influence of discipline work, headmaster supervision and motivation to elementary school teacher performance. The result of research refer to discipline work, headmaster supervision and together motivation influenced to elementary school teacher performance in SMA Negeri di Kabupaten Jepara. And in test, point to Sig all value under 0,05. Sp the result can be conclude such as : Discipline work influenced positive and significally to elementary school teacher performance in SMA Negeri di Kabupaten Jepara. Headmaster supervision positive influence and significally to elementary school teacher performance in SMA Negeri di Kabupaten Jepara. And Motivation is positive influence and significally to elementary school teacher performance in SMA Negeri di Kabupaten Jepar. Keyword : Discipline Work, Headmaster Supervision, Motivation Work Â and Teacher Performance